Development of the Mental Synthesis Evaluation Checklist (MSEC): A Parent-Report Tool for Mental Synthesis Ability Assessment in Children with Language Delay - Braverman, Julia (Children (Basel), 2018)
Mental synthesis is the conscious purposeful process of synthesizing novel mental images from objects stored in memory. Mental synthesis ability is essential for understanding complex syntax, spatial prepositions, and verb tenses. In typical children, the timeline of mental synthesis acquisition is highly correlated with an increasing vocabulary. Children with Autism Spectrum Disorder (ASD), on the other hand, may learn hundreds of words but never acquire mental synthesis. In these individuals, tests assessing vocabulary comprehension may fail to demonstrate the profound deficit in mental synthesis. We developed a parent-reported Mental Synthesis Evaluation Checklist (MSEC) designed to assess mental synthesis acquisition in ASD children. The psychometric quality of MSEC was tested with 3715 parents of ASD children. Internal reliability of the 20-item MSEC was good (Cronbach’s alpha >0.9). MSEC exhibited adequate test–retest reliability; good construct validity, supported by a positive correlation with the Autism Treatment Evaluation Checklist (ATEC) Communication subscale; and good known group validity reflected by the difference in MSEC scores for children of different ASD severity levels. The MSEC questionnaire is copyright-free and can be used by researchers as a complimentary subscale for the ATEC evaluation. We hope that the addition of MSEC will make the combined assessment more sensitive to small steps in a child’s development. As MSEC does not rely on productive language, it may be an especially useful tool for assessing the development of nonverbal and minimally verbal children.